Aging-resistant composite modifier for asphalt and preparation method thereof

CN123003185APending Publication Date: 2026-10-30THE FIRST CONSTR ENG COMPANY LTD OF CHINA CONSTR SECOND ENG BUREAU +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611216109.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-12
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0006]针对现有技术的沥青填料界面粘结弱、抗老化组分易迁移流失、废胶粉易脱落、施工易离析、长期耐老化路用性能不足的问题,本发明提供了一种沥青用耐老化复合改性填料及其制备方法

Benefits of technology

本发明通过矿物载体的孔隙结构固载抗老化功能组分,将纳米紫外屏蔽组分与载体原位复合形成稳定固载结构,可避免物理干拌工艺导致的纳米组分硬团聚问题,同时依托载体的物理束缚作用减少小分子抗老化组分在沥青热储、长期服役过程中的溶出迁移,使抗老化组分能够长期稳定发挥紫外阻隔与自由基捕获作用,有效解决了现有物理复配型填料抗老化功能衰减快、紫外屏蔽效率不足的缺陷,使沥青胶浆在长期强紫外辐照、热氧耦合作用下仍能保持稳定的胶体结构与路用性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123003185A_ABST
    Figure CN123003185A_ABST
Patent Text Reader

Abstract

The application discloses an anti-aging composite modified filler for asphalt, and is characterized in that: alkaline mineral powder activated by heat and acid etching is used as a functional carrier, a nano titanium dioxide ultraviolet shielding component and a hindered amine light stabilizing component are fixed in the pore structure of the carrier by using a negative pressure immersion process, modified waste rubber powder with an affinity group activated and grafted by low-temperature plasma and a mineral synergistic filler with a surface modified by a silane coupling agent are matched, the particle size gradient of each component is matched according to the requirement of continuous dense grading, and the finished product is obtained by uniform high-speed blending at room temperature, so that the product can directly replace traditional limestone powder and be applied to the production of asphalt mixtures of various grades of roads, and is suitable for the existing conventional hot-mix asphalt construction process. The application can effectively strengthen the interfacial chemical bonding strength between the asphalt component and the anti-aging functional component, inhibit the migration and loss of the anti-aging functional component during high-temperature heat storage and long-term service, and avoid the problems of hard agglomeration of the nano functional component, interface peeling and falling of the waste rubber powder and construction mixing segregation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of asphalt aging-resistant composite modified filler technology, and more particularly to an asphalt aging-resistant composite modified filler and its preparation method. Background Technology

[0002] Asphalt pavement is the mainstream paving form for high-grade highways in my country. As a core component of asphalt mixtures, fillers account for 5% to 10% of the total mass of aggregates, playing a crucial role in filling gaps between aggregates, strengthening the bonding of asphalt mastic, and improving the structural stability of the mixture. With the continuous advancement of highway network construction in high-altitude, high-UV areas in western my country, and the large-scale promotion of long-life pavement technology, the industry's performance requirements for asphalt fillers have gradually shifted from basic filling functions to resistance to long-term UV aging, adaptability to road performance across the entire temperature range, and reduction of maintenance costs throughout the entire life cycle. Simultaneously, the low-carbon development requirements of utilizing road solid waste resources are being considered, making this a core research and development direction in the field of road engineering materials.

[0003] Currently, asphalt fillers used in engineering are mainly divided into two categories. The first category is traditional limestone powder filler, which is also the most commonly used conventional solution. It obtains mineral powder that meets basic fineness requirements by mechanically crushing limestone. It relies on the physical adsorption of alkaline mineral components and acidic resin components in asphalt to form a mortar structure. It has the advantages of readily available raw materials, low processing costs, and mature construction technology, and can meet the basic usage requirements of ordinary pavements in areas with normal temperature and low radiation. However, this type of filler itself does not have active anti-aging function, its density differs greatly from that of asphalt, and its specific surface area is at a low level. The interfacial bonding with asphalt relies only on weak physical adsorption. Under the coupled effects of strong ultraviolet long-term radiation, high-temperature thermal storage, and freeze-thaw cycles, the asphalt components rapidly oxidize, age, and become brittle. The interface is prone to water damage and delamination. Moreover, the carbon emissions during the raw material mining process are high, making it difficult to adapt to the performance requirements of long-life pavements and the needs of low-carbon construction.

[0004] The second type is physically compounded modified fillers, which are modified by adding nano-UV shielding agents, small molecule light stabilizers, waste rubber powder and other modified components to traditional mineral powder through dry mixing. Relying on the light blocking effect of UV shielding agents, the free radical scavenging effect of light stabilizers and the elastic toughening effect of waste rubber powder, the aging resistance and low temperature crack resistance of asphalt mastic are improved. At the same time, the resource utilization of industrial solid waste is realized. This is the mainstream direction of modified filler research and development in recent years. However, this type of physical blending process has obvious performance shortcomings: nano-UV shielding agents are prone to hard agglomeration due to lack of carrier binding, resulting in poor dispersion uniformity and insufficient UV shielding efficiency; small molecule light stabilizers are easily dissolved and leached by oil in asphalt, and are lost with oil migration during long-term heat storage and service, resulting in insufficient long-term anti-aging effect; waste rubber powder is not modified at the interface, has poor compatibility with asphalt, and is prone to falling off from the rubber interface under long-term load and water erosion, resulting in rapid decay of low-temperature toughening effect; at the same time, the compound components have large density differences and no systematic gradation control is performed, which easily leads to segregation during construction and mixing, resulting in uneven local performance of the pavement and making it difficult to ensure the long-term service stability of long-life pavements.

[0005] To address the performance shortcomings of existing modified fillers in practical applications, it is necessary to develop new modified fillers that meet the requirements for long service life of asphalt pavements. This will solve common problems such as rapid performance degradation and poor construction adaptability of existing technologies, and is of great practical significance for improving the service life of asphalt pavements in high-altitude and high-irradiation areas, reducing the total life-cycle maintenance cost, and promoting the high-value utilization of road solid waste. Summary of the Invention

[0006] To address the problems of weak interfacial bonding, easy migration and loss of anti-aging components, easy shedding of waste rubber powder, easy segregation during construction, and insufficient long-term aging resistance in existing asphalt fillers, this invention provides an aging-resistant composite modified filler for asphalt and its preparation method.

[0007] To achieve the above objectives, the present invention adopts the following technical solution: an aging-resistant composite modified filler for asphalt, comprising the following components by weight: 40-60 parts of surface-reconstructed calcined coal gangue matrix, 20-35 parts of loaded anti-aging component, and 10-25 parts of interface-modified coating layer; wherein the surface-reconstructed calcined coal gangue matrix is ​​a heterogeneous, rough, rigid particle with calcined activated coal gangue as the core, and sodium calcium-based bentonite sheets are embedded and anchored on the microcracks and pit defects on the surface of the calcined coal gangue particles through mechanochemical action, wherein the sodium calcium-based bentonite sheets do not completely cover the core surface of the coal gangue, retaining the porous adsorption sites of the coal gangue itself. The loaded anti-aging component is a fibrous anti-aging unit formed by in-situ depositing and anchoring nano-cerium dioxide particles in the open pores of sepiolite fibers as a support carrier, and grafting a hindered amine light stabilizer onto the silanol sites on the surface of sepiolite fibers via silicon-oxygen covalent bonds. This component does not contain free nano-cerium dioxide or free hindered amine light stabilizer molecules. The interface-modified coating layer is an elastic micro-powder with amino active sites introduced on the surface of the rubber powder by grafting an amino-active site onto the surface of the rubber powder through a silane coupling agent. The elastic micro-powder is uniformly and continuously coated on the outer surface of the mixed core particles formed by the surface reconstruction of calcined coal gangue matrix and the loaded anti-aging component through the bonding effect of cationic slow-cracking asphalt emulsion, forming an elastic transition interface layer of uniform thickness. The components work together to form a three-layer stable core-shell structure of "rigid core - anti-aging fiber intermediate phase - elastic shell".

[0008] Furthermore, in the surface-reconstructed calcined coal gangue base material, the calcined coal gangue raw material is selected from coal gangue produced by coal mining in underground coal mines with a fixed carbon content of 15%-25%, a kaolinite content of not less than 60%, and a total sulfur content of not more than 1%. After the coal gangue is crushed to a particle size of less than 5 mm with a particle size of not less than 95%, it is heated from room temperature to 750-850℃ at a uniform heating rate of 5℃ / min and kept at that temperature for 1.5-2.5 hours. During the calcination process, a small amount of air is introduced to ensure complete oxidation of residual carbon. After calcination, the residual carbon content of the coal gangue is not more than 1%. After natural cooling, it is ground to 200-300 mesh by a closed-circuit roller mill. The sodium-modified calcium-based bentonite used is modified bentonite obtained by sodium modification of calcium-based bentonite ore with sodium carbonate at 4% of the bentonite mass for 24 hours, followed by drying and grinding to 1200 mesh. The mass ratio of sodium-modified calcium-based bentonite to calcined coal gangue is 1:9. The thickness of the bentonite sheets embedded on the surface of calcined coal gangue under high-speed shear mechanical force is 20-50 nm. The overall specific surface area of ​​the base material is 400-500 m² / kg. At this specific surface area, the base material can adsorb appropriate amounts of saturated and aromatic components in the asphalt to form a stable asphalt layer. It will not cause asphalt hardening due to excessive adsorption of light components, nor will it cause weak interfacial adhesion due to insufficient adsorption capacity.

[0009] Furthermore, in the supported anti-aging component, the acidified sepiolite wool is made from low-impurity sepiolite ore wool with a fiber length of 0.5-2 mm. It is acidified and stirred for 2 hours in 1 mol / L hydrochloric acid solution at 60°C and a solid-liquid ratio of 1:10 to remove carbonate impurities from the pores and open the internal channels. After washing until there are no chloride ions left, drying, and air-flow loosening, the acidified sepiolite wool has a porosity of not less than 60% and a pore volume of not less than 0.4 cm³ / g. The sepiolite fiber crystal structure is complete and without breakage. The nano-cerium dioxide loaded in the pores of the sepiolite wool is nanoparticles generated by in-situ hydrolysis and deposition of cerium hexahydrate under alkaline conditions. The loading amount of nano-cerium dioxide is 15%-25% of the mass of the acidified sepiolite wool. The average particle size of nano-cerium dioxide is 10-20 nm, in which the molar ratio of trivalent cerium to tetravalent cerium is 3:7, which has a suitable oxygen vacancy concentration and can efficiently capture peroxy free radicals generated by thermal and photo-oxidative aging of asphalt. The hindered amine light stabilizer 944 is a hindered amine light stabilizer whose molecular chain segments carry triethoxysilane active groups. It is fixed by Si-O-Si covalent bonding formed by the alcoholysis reaction of triethoxysilane with the silanol groups on the surface of sepiolite. The grafting loading is 8%-12% of the mass of acidified sepiolite fibers. The hindered amine light stabilizer after grafting will not be dissolved by the oil in the asphalt and can play a light stabilizing role at the filler interface for a long time.

[0010] Furthermore, in the interface-modified coating layer, the ultrafine activated waste rubber powder is made from waste tire tread rubber of heavy-duty trucks. After removing steel wire and fiber impurities, it is crushed to 40 mesh coarse rubber powder at room temperature. It is then subjected to dynamic stress desulfurization using a twin-screw extruder without the addition of chemical desulfurization additives. The strong shearing action of the screw selectively breaks the SS crosslinking bonds in the vulcanized rubber while preserving the integrity of the rubber carbon-carbon main chain. The desulfurized rubber compound is then air-cooled and ultrafinely ground to obtain a powder particle size of 1200-1500 mesh. The gel content of the rubber powder is controlled at 60%-70%, and it has suitable crosslinking elasticity. The silane coupling agent used in the grafting modification is pre-hydrolyzed and activated γ-aminopropyltriethoxysilane. After being hydrolyzed for 30 minutes under weakly acidic conditions with a pH of 4.5-5.5, the coupling agent is spray-grafted to form covalent bonds with the active hydroxyl groups generated by bond breaking on the surface of the rubber powder. The coating amount of the coupling agent is 2%-3% of the mass of the ultrafine activated waste rubber powder. After grafting, the surface of the rubber powder is uniformly distributed with amino active sites that can chemically bond with the carboxyl and carbonyl groups contained in the asphalt and gum. There is no multilayer adsorption or agglomeration of the coupling agent.

[0011] Furthermore, the composite modified filler is granulated and sieved to form continuously graded particles with an overall particle size distribution of 100-400 mesh, wherein the 200 mesh sieve residue rate is no more than 5% and the 400 mesh passing rate is no more than 5%, which can achieve the densest packing when filled in the gaps between asphalt mixture aggregates. The apparent density of the filler is 1.2-1.6 g / cm³, which is close to the apparent density of limestone powder commonly used in road engineering. During construction and mixing, the filler will not segregate due to density difference. The average shielding rate of the filler in the 200-400nm ultraviolet band is not less than 90%. This band is the core ultraviolet band that causes photo-oxidative aging of asphalt. The filler dispersed in asphalt can form a continuous ultraviolet shielding network. The contact angle between the filler and No. 70 road petroleum asphalt at room temperature is no more than 30°, and the surface wettability is excellent. After bonding with asphalt, it will not produce interfacial voids that cause water damage. Under the condition of hot storage at 163℃ for 48 hours, the migration rate of the anti-aging active components is no more than 2%, and there is no performance degradation problem caused by rapid precipitation of anti-aging components.

[0012] Furthermore, the entire preparation process employs a combination of mechanochemical modification, covalent bond loading, and low-temperature granulation coating. There are no harsh reaction conditions involving high temperature and pressure, no toxic or harmful solvent emissions, and all sieve residues and undersize materials are recycled during production, resulting in no solid waste discharge. Specifically, the process includes the following steps: S1. Preparation of surface-reconstructed calcined coal gangue base material: After crushing the raw coal gangue ore that meets the composition requirements, it is calcined at high temperature and uniform speed to remove residual carbon and activate the pozzolanic activity. After grinding to the specified particle size, it is mixed with pre-prepared sodium-modified calcium-based bentonite. Through the mechanochemical action generated by high-speed shearing, the exfoliated bentonite nanosheets are embedded and anchored at the surface defect sites of the calcined coal gangue. After drying and secondary grinding to adjust the specific surface area, a surface-heterogeneous and rough reconstructed base material is obtained. No organic chemical modifiers are used in this step to avoid introducing impurities that affect the asphalt performance. S2. Preparation of the supported anti-aging component: The high-porosity sepiolite fiber obtained by acid modification is uniformly dispersed in an ethanol aqueous solution. A cerium source precursor is added to generate nano-cerium dioxide through in-situ precipitation reaction and anchor it in the pore structure of the sepiolite fiber. Then, a hindered amine light stabilizer with a triethoxysilane active group is added to carry out a covalent grafting reaction. After centrifugation to remove unreacted free components, vacuum drying and fiber loosening are performed to obtain the anti-aging component. This step avoids the migration of the anti-aging component through a dual fixation effect. S3. Preparation of interface-modified coating material: Clean waste tire tread rubber powder is activated by twin-screw dynamic stress desulfurization and then ultra-finely ground. The fluidized rubber powder is spray-grafted and modified with a pre-hydrolyzed silane coupling agent ethanol solution. After hot air curing, activated waste rubber powder with amino active sites on the surface is obtained. This step adopts a chemical-free desulfurization process to avoid the introduction of low molecular weight impurities. S4. Composite Coating Molding: Surface-reconstructed calcined coal gangue base material and loaded anti-aging components are put into a high-speed mixer and pre-mixed evenly at room temperature. Atomized spraying of cationic slow-cracking asphalt emulsion forms a thin adhesive layer on the particle surface. Then, activated waste rubber powder is added and continuously mixed at high speed under medium temperature conditions, so that the rubber powder adheres evenly to and coats the surface of the mixed core particles to form a continuous elastic shell layer. After low-temperature drying and screening by a double-layer vibrating screen, the finished filler is obtained. This step adopts a low-temperature coating process to avoid the decomposition of anti-aging components and the aging and degradation of rubber powder caused by high temperature.

[0013] Furthermore, in S1, after the raw coal gangue ore is coarsely crushed by a jaw crusher and finely crushed by an impact crusher, the proportion of particles with a diameter less than 5mm is not less than 95%. The crushed coal gangue is then fed into a rotary kiln for calcination. The rotary kiln speed is set to 2r / min to ensure uniform heating of the coal gangue. The calcination temperature is controlled at 750-850℃, and the calcination holding time is 1.5-2.5h. When the temperature is below 750℃, the kaolinite in the coal gangue cannot be completely converted into metakaolinite, the volcanic ash activity is insufficient, and the residual carbon is not completely removed. When the temperature is above 850℃, the coal gangue undergoes over-burning and sintering, internal pore collapse, and a significant decrease in specific surface area. After calcination, the coal gangue is naturally cooled to room temperature and then fed into a closed-circuit roller mill for grinding. The calcined coal gangue powder is then separated into 200-300 mesh particles by a classifier. Sodium-modified calcium-based bentonite is prepared in advance. The calcium-based bentonite ore is dried and ground to 200 mesh, then 4% sodium carbonate (by weight of bentonite) and an appropriate amount of deionized water are added and mixed evenly. The mixture is allowed to stand for 24 hours to complete the sodium modification, and after drying, it is ground to 1200 mesh for later use. The calcined coal gangue powder and sodium-modified calcium-based bentonite are fed into a high-speed shear mixer at a mass ratio of 9:1, with the shearing speed set to 3000-4000 rpm. During the shearing process, 5%-8% of deionized water mist, accounting for 5%-8% of the mass of the mixed powder, is continuously sprayed through a high-pressure atomizing nozzle. The water mist particle size is controlled at 10-20μm, forming an extremely thin water film on the particle surface to promote the exfoliation of bentonite sheets. The shearing and mixing time is 8-12 minutes. Under the action of mechanical force, the exfoliated bentonite nanosheets are firmly embedded in the defects on the surface of the coal gangue. After mixing, the powder is sent to a belt dryer and dried at 105℃ until the moisture content is no more than 0.5%. After secondary grinding, the specific surface area is adjusted to 400-500m² / kg to obtain surface-reconstructed calcined coal gangue base material.

[0014] Furthermore, the preparation process of the acid-modified sepiolite wool in S2 is as follows: select sepiolite raw wool with a fiber length of 0.5-2mm, remove talc and quartz impurities, and then immerse it in a 1mol / L supernatant hydrochloric acid solution with a solid-liquid ratio of 1:10. Acidify by stirring at 300rpm for 2 hours in a constant temperature water bath at 60℃ to dissolve and remove carbonate impurities in the pores, open up the internal channels, and retain the fiber crystal structure. After acidification, filter the solid phase using a Buchner funnel, and repeatedly wash the filter cake with 60℃ deionized water until the pH of the filtrate is 7 and no chloride ion residue is detected by silver nitrate solution. Dry the filter cake in a forced air at 105℃ for 4 hours and then loosen it with compressed air at 0.6MPa to obtain dispersed and non-agglomerated fibrous acidified sepiolite wool with a porosity of not less than 60% and a pore volume of not less than 0.4cm³ / g. Acidified sepiolite fibers were dispersed in a 50% (v / v) ethanol aqueous solution at a solid-liquid ratio of 1:20 and dispersed at a high speed of 2000 rpm for 30 min to obtain a uniform suspension. Cerium nitrate hexahydrate was added at a ratio of 15%-25% nano-cerium dioxide loading and stirred until completely dissolved. Then, 10% (w / w) dilute ammonia solution was slowly added dropwise at a rate of 2 mL / min to adjust the pH of the system to 8-9. After the addition was completed, the system was heated to 70℃ and stirred at a constant speed of 400 rpm for 2 h to allow the in-situ generated nano-cerium dioxide to be uniformly deposited in the pores and surface of the sepiolite fibers. The average particle size of the nano-cerium dioxide was 10-20 nm, and the molar ratio of trivalent cerium to tetravalent cerium was 3:7. Add hindered amine light stabilizer 944 with triethoxysilyl groups at a grafting loading ratio of 8%-12%. After stirring and dissolving, heat the system to 80℃ and stir for 3 hours to allow the light stabilizer to be grafted onto the hydroxyl sites on the surface of sepiolite fibers via silicon-oxygen covalent bonds. After the reaction is complete, centrifuge at 3000 rpm for 10 minutes to separate the solid phase. Discard the supernatant containing unreacted free components. Dry the solid phase at 80℃ and -0.09 MPa vacuum for 12 hours. The loaded anti-aging component is obtained by fiber decomposition.

[0015] Furthermore, in S3, after the waste tire tread rubber blocks are manually cleaned of metal and fiber impurities, they are fed into a room temperature rubber crusher under circulating water cooling conditions and crushed into 40-mesh coarse rubber powder. During the crushing process, the temperature of the rubber powder does not exceed 80°C to avoid excessive degradation of the rubber molecular chains. The coarse rubber powder is fed into a parallel twin-screw extruder with a length-to-diameter ratio of 40:1 for stress desulfurization activation. The five temperature zones of the barrel are set to 120℃, 160℃, 180℃, 200℃ and 180℃ respectively from the feeding section to the extrusion section. The screw speed is set to 300 rpm. The rubber powder is subjected to strong shearing in the shearing section to selectively break the sulfur-sulfur cross-linking bonds. No chemical desulfurization aids or softeners are added. The extruded desulfurized rubber strip is cooled to room temperature by an air-cooled conveyor belt and then fed into an ultrafine turbo mill to be ground to 1200-1500 mesh under cold air circulation to obtain ultrafine desulfurized rubber powder with a gel content of 60%-70% and retaining suitable cross-linking elasticity. Ultrafine desulfurized rubber powder is fed into a fluidized bed modification device, and 100°C hot air is introduced from the bottom to keep the rubber powder in a uniform fluidized state. γ-aminopropyltriethoxysilane is prepared into an ethanol aqueous solution with a mass concentration of 20%. The pH of the solution is adjusted to 4.5-5.5 with glacial acetic acid. The solution is allowed to stand for hydrolysis for 30 minutes to fully activate the coupling agent. The coupling agent solution is then uniformly sprayed onto the surface of the fluidized rubber powder through a high-pressure atomizing nozzle. The amount of coupling agent is calculated as 2%-3% of the mass of the ultrafine activated waste rubber powder. After spraying, the solution is kept in a fluidized state and heat-cured for 20 minutes to allow the coupling agent to form covalent grafts with the active hydroxyl groups on the surface of the rubber powder. At the same time, residual ethanol and water are removed to obtain activated waste rubber powder.

[0016] Furthermore, in step S4, the surface-reconstructed calcined coal gangue base material and the loaded anti-aging component are weighed according to the proportion and fed into a toothed paddle high-speed mixer. The speed of the premixing stage is set to 1500 rpm, the mixing chamber is kept at 25°C, and the premixing time is 5 min, so that the fibrous anti-aging component is evenly dispersed between the base material particles to form a uniform mixed dry powder. After premixing, reduce the mixer speed to 1000 rpm and spray a cationic slow-cracking asphalt emulsion with a solid content of 50% into the mixing chamber through a high-pressure atomizing nozzle. The emulsion demulsification time is not less than 2 hours, and the spraying amount accounts for 3%-5% of the total mass of the mixed powder. The droplet size of the emulsion is controlled to be 20-30 μm, so that it adheres evenly to the surface of the particles to form a thin bonding layer and does not cause excessive agglomeration of particles. After the emulsion is sprayed, the activated waste rubber powder is weighed according to the ratio and added to the mixer at a uniform speed through the side feed port. The powder addition time is controlled at 2 minutes. After the powder addition is completed, the speed of the mixer is increased to 2500 rpm, and circulating hot water is introduced into the jacket of the mixing chamber to control the temperature inside the chamber at 60-70℃. The mixing is continued for 10 minutes, so that the activated waste rubber powder adheres evenly to the surface of the core particles under the action of particle collision, forming a continuous and uniform elastic coating layer. This temperature range can ensure that the water in the emulsion evaporates slowly, avoid rapid demulsification and rubber powder agglomeration, and at the same time, it will not cause the grafted light stabilizer to decompose or the rubber powder to age due to excessive temperature. After mixing, the material is sent to a hot air circulating drying box and dried at 110-120℃ until the moisture content of the material is no more than 1%. It is then screened using a double-layer vibrating screen with 100 mesh and 400 mesh. The material between the two screens is used as the finished product filler. The large particles retained on the 100 mesh screen are returned to the ultrafine grinding process for reprocessing, and the fine material under the 400 mesh screen is returned to the premixing process as the core powder for regranulation. The material utilization rate in the production process reaches 100%.

[0017] The present invention has the following beneficial effects: This invention utilizes the porous structure of a mineral carrier to immobilize anti-aging functional components, forming a stable immobilized structure by in-situ combining nano-UV shielding components with the carrier. This avoids the hard agglomeration problem of nano-components caused by physical dry mixing processes. At the same time, the physical binding effect of the carrier reduces the dissolution and migration of small-molecule anti-aging components during asphalt thermal storage and long-term service, enabling the anti-aging components to stably exert their UV blocking and free radical capture effects over a long period. This effectively solves the defects of existing physically compounded fillers, such as rapid decay of anti-aging function and insufficient UV shielding efficiency, allowing asphalt mastic to maintain a stable colloidal structure and road performance even under long-term strong UV radiation and thermo-oxygen coupling.

[0018] This invention modifies the interface of waste rubber powder components by performing interface activation, constructing a reactive interface layer with high affinity to asphalt components on the surface of the rubber powder. This strengthens the interfacial bonding strength between the rubber powder and asphalt mortar, preventing the rubber powder from peeling off from the mortar interface under long-term water erosion and vehicle dynamic loads, and continuously exerting elastic toughening effects. It effectively solves the defects of poor compatibility between waste rubber powder and asphalt and rapid decay of low-temperature toughening effect with service cycle in existing compound fillers, enabling asphalt mixtures to maintain stable crack resistance under low-temperature environments and repeated freeze-thaw cycles.

[0019] This invention improves the chemical adsorption between filler and asphalt components by synergistically regulating the gradation of multi-component filler components and combining it with surface activation treatment of mineral components. This enhances the chemical adsorption between filler and asphalt components and avoids the segregation of different density components during construction mixing and high-temperature thermal storage. It effectively solves the defects of traditional mineral powder filler with weak interfacial bonding and easy segregation of compound filler during construction, which leads to uneven local performance of the pavement. It can be adapted to conventional asphalt mixture construction technology and can meet the construction requirements of different grades of asphalt pavement without additional adjustment of construction parameters.

[0020] This technical solution is compatible with various high-value utilization paths for industrial solid waste and can adapt to the construction needs of long-life asphalt pavement in different service environments such as high-altitude areas with strong ultraviolet radiation, high-temperature and rainy areas, and frigid areas, thus possessing good engineering promotion and application value. Attached Figure Description

[0021] Figure 1This is a schematic flowchart of a method for preparing an aging-resistant composite modified filler for asphalt according to the present invention. Figure 2 The basic physical properties of the filler in this invention are grouped into a bar chart; Figure 3 A bar chart showing the grouped aging performance of asphalt mastic in this invention; Figure 4 The scatter plot of the correlation between the migration rate of the anti-aging component of the filler and the ultraviolet shielding rate in this invention; Figure 5 Radar chart showing the combined performance of the optimal embodiment of this invention and traditional packing materials. Detailed Implementation

[0022] The following will refer to the appendices in the embodiments of the present invention. Figures 1-5 The technical solutions in the embodiments of the present invention are clearly and completely described herein. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0023] Example 1 Raw material pretreatment: Coal gangue from a coal mine in Shanxi Province was selected. After testing, the carbon content was fixed at 18%, the kaolinite content was 65%, and the total sulfur content was 0.7%, which met the requirements of the base material. Sodium-modified calcium-based bentonite was self-made. It was made from calcium-based bentonite ore with 72% montmorillonite content from Inner Mongolia. It was modified by sodium carbonate (4% of the bentonite mass) for 24 hours, dried and ground to 1200 mesh for later use. The sepiolite fibers are made from fibrous sepiolite ore from Hebei Province, with fiber lengths of 0.5-2 mm and a sepiolite content of 85%. Cerium nitrate hexahydrate is an analytical grade reagent with a purity of 99%. The hindered amine light stabilizer 944 with triethoxysilyl groups is an industrial grade product with a silane active group grafting rate of 95%. Waste tire tread rubber is taken from waste truck tires, and steel wires and fiber impurities are manually removed before use; γ-aminopropyltriethoxysilane is industrial grade with a purity of 98%; cationic slow-cracking asphalt emulsion is commercially available PC-3 type with a solid content of 50% and a demulsification time of 2.5 hours; No. 70 Grade A road petroleum asphalt meets the requirements of JTG F40-2004 specification.

[0024] S1 Preparation of Surface Reconstructed Calcined Coal Gangue Base Material: The raw coal gangue ore was coarsely crushed by a jaw crusher and finely crushed by an impact crusher, and screened to obtain particles with a diameter of less than 5 mm, accounting for 96%; the crushed coal gangue was fed into a rotary kiln, and the temperature was raised from room temperature to 750℃ at a uniform heating rate of 5℃ / min. The rotary kiln speed was set to 2r / min to ensure uniform heating of the material. The material was calcined at this temperature for 2.5h. During the calcination process, a small amount of air was introduced to ensure complete oxidation of residual carbon. After calcination, the material was naturally cooled, and the residual carbon content of the coal gangue was found to be 0.6%. Calcined coal gangue was ground in a closed-circuit roller mill and separated into 200-300 mesh powder by a classifier. The calcined coal gangue powder and pretreated sodium calcium-based bentonite were fed into a high-speed shear mixer at a mass ratio of 9:1. The shearing speed was set to 3000 rpm. During the shearing process, 5% of the mixed powder mass of deionized water mist was continuously sprayed through a high-pressure atomizing nozzle. The water mist particle size was controlled to be 10-20 μm, forming an extremely thin water film on the particle surface to promote the peeling of bentonite lamellae. The shearing and mixing time was 12 min. After mixing, the powder was sent to a belt dryer and dried at 105℃ to a moisture content of 0.4%. The specific surface area was adjusted to 420 m² / kg by secondary grinding. Electron microscopy showed that the thickness of the bentonite lamellae embedded on the surface of the coal gangue was 20-40 nm, resulting in a surface-reconstructed calcined coal gangue matrix.

[0025] This step constructs a heterogeneous rough surface and controls an appropriate specific surface area through mechanochemical action, which can prevent the base material from over-adsorbing light asphalt components and causing hardening. At the same time, it enhances the mechanical interlocking force with asphalt and solves the defects of smooth surface and weak interfacial adhesion of solid waste base filler.

[0026] S2 Preparation of Supported Anti-aging Components: First, acidified sepiolite wool is prepared. After removing talc and quartz impurities from the raw sepiolite wool, it is immersed in a 1 mol / L high-purity hydrochloric acid solution with a solid-liquid ratio of 1:10. The solution is acidified by stirring at 300 rpm for 2 hours in a constant temperature water bath at 60℃ to dissolve carbonate impurities in the pores and open up the internal channels. After acidification, the solid phase was filtered using a Buchner funnel. The filter cake was repeatedly washed with deionized water at 60°C until the pH of the filtrate was 7. No chloride ions were found to be present after testing with silver nitrate solution. The filter cake was dried in a forced-air dryer at 105°C for 4 hours and then loosened by compressed air at 0.6 MPa to obtain dispersed, non-agglomerated fibrous acidified sepiolite fibers. The porosity was 62%, the pore volume was 0.41 cm³ / g, and the fiber crystal structure was intact and without breakage.

[0027] Acidified sepiolite fibers were dispersed in a 50% (v / v) ethanol aqueous solution at a solid-liquid ratio of 1:20 and dispersed at 2000 rpm for 30 min to obtain a uniform suspension. Cerium nitrate hexahydrate was added at a loading ratio of 15% nano-cerium dioxide, and stirred until completely dissolved. Then, 10% (w / w) dilute ammonia solution was slowly added dropwise at a rate of 2 mL / min to adjust the pH of the system to 8.2. After the addition was complete, the system was heated to 70℃ and stirred at a constant speed of 400 rpm for 2 h. During the reaction, cerium nitrate hexahydrate underwent a hydrolysis precipitation reaction with ammonia solution. The reaction formula is as follows: The resulting nano-cerium dioxide particles are uniform in size and are anchored within the carrier through the physical confinement effect of the open pores of sepiolite. They do not diffuse or migrate in the lightweight asphalt components and can play a long-term role in capturing oxygen vacancy free radicals, blocking the chain reaction of thermo-oxidative and photo-oxidative aging, and solving the problem of reduced protective efficiency caused by the easy agglomeration and migration of nano-cerium dioxide. After in-situ precipitation, hindered amine light stabilizer 944 with triethoxysilyl groups is added at a ratio of 8% of the hindered amine light stabilizer grafting loading. After stirring and dissolving, the system is heated to 80℃ and stirred for 3 hours. The light stabilizer molecules undergo an alcoholysis grafting reaction with the silanol groups on the surface of sepiolite. The reaction formula is as follows: The grafting reaction enables the hindered amine light stabilizer molecules to be firmly bound to the surface of sepiolite fibers through silicon-oxygen covalent bonds. There are no free small molecule stabilizers, and they will not be dissolved and released by saturated fractions or aromatic fractions in asphalt. They can continuously decompose the peroxides generated by aging in the interface region between filler and asphalt, thereby improving long-term light stability and solving the defects of small molecule light stabilizers that are easy to precipitate and have insufficient long-term performance.

[0028] After the reaction was completed, the solid phase was separated by centrifugation at 3000 rpm for 10 min. The supernatant containing unreacted free components was discarded. The solid phase was dried at 80℃ and -0.09 MPa vacuum for 12 h. The supported anti-aging component was obtained by fiber loosening. The average particle size of the nano-cerium dioxide was 12 nm, the molar ratio of trivalent cerium to tetravalent cerium was 2.8:7.2, and it had a suitable oxygen vacancy concentration.

[0029] S3 Preparation of Interface Modified Coating Material: Clean waste tire tread rubber blocks are fed into a room temperature rubber crusher under circulating water cooling conditions and crushed into 40 mesh coarse rubber powder. The temperature of the rubber powder during the crushing process does not exceed 75℃ to avoid excessive degradation of rubber molecular chains. The coarse rubber powder was fed into a parallel twin-screw extruder with a length-to-diameter ratio of 40:1 for stress desulfurization activation. The five temperature zones of the barrel were set to 120℃, 160℃, 180℃, 200℃ and 180℃ respectively from the feeding section to the extrusion section. The screw speed was set to 300 rpm. The rubber powder was subjected to strong shearing in the shearing section, which selectively broke the sulfur-sulfur cross-linking bonds and preserved the integrity of the carbon-carbon backbone of the rubber without the addition of chemical desulfurization additives. The extruded desulfurized rubber strips were cooled to room temperature by an air-cooled conveyor belt and then fed into an ultrafine turbine mill to be ground to 1200 mesh under cold air circulation. The gel content of the rubber powder was found to be 68%, retaining suitable cross-linking elasticity. The ultrafine desulfurized rubber powder was then fed into a fluidized bed modification device, where 100°C hot air was introduced from the bottom to keep the rubber powder in a uniform fluidized state. γ-aminopropyltriethoxysilane was prepared into a 20% (w / w) ethanol aqueous solution, and the pH of the solution was adjusted to 4.8 with glacial acetic acid. The solution was allowed to stand for 30 minutes to fully activate the coupling agent. The coupling agent solution was sprayed evenly onto the surface of the fluidized rubber powder through a high-pressure atomizing nozzle at a ratio of 2% of the coupling agent coating amount. After spraying, the solution was kept in a fluidized state and heat-cured for 20 minutes to allow the coupling agent to form covalent grafts with the active hydroxyl groups generated by bond breaking on the surface of the rubber powder. At the same time, residual ethanol and water were removed to obtain activated waste rubber powder. The surface of the rubber powder was found to have uniform amino distribution and no multilayer adsorption or agglomeration of the coupling agent. This step introduces amino active sites through silane grafting, which can form chemical bonds with carboxyl and carbonyl groups in asphalt, thus solving the defects of poor bonding and easy detachment between waste rubber powder and asphalt.

[0030] S4 Composite Coating Molding: Weigh 60 parts by weight of surface-reconstructed calcined coal gangue base material and 28 parts by weight of loaded anti-aging component and put them into a toothed paddle high-speed mixer. Set the premixing speed to 1500 rpm, keep the mixing chamber at 60℃, and the premixing time to 5 min, so that the fibrous anti-aging component is evenly dispersed between the base material particles to form a uniform mixed dry powder. After premixing, reduce the mixer speed to 1000 rpm. Spray 3% (by weight) of cationic slow-cracking asphalt emulsion into the mixing chamber through a high-pressure atomizing nozzle. Control the emulsion droplet size to 20-30 μm, ensuring it adheres evenly to the particle surface to form a thin bonding layer without excessive particle agglomeration. Add 10 parts by weight of activated waste rubber powder over 2 minutes. After adding the powder, increase the mixer speed to 2500 rpm and circulate hot water into the mixing chamber jacket to stabilize the temperature. Continue mixing for 10 minutes. The activated waste adhesive powder is uniformly adhered to the surface of the core particles through particle collision, forming a continuous and uniform elastic coating layer. After mixing, the material is sent to a hot air circulating drying oven and dried at 110℃ until the moisture content is 0.8%. It is then sieved using a double-layer vibrating screen with 100 mesh and 400 mesh screens. The material between the two screens is used as the finished filler. Large particles retained on the 100 mesh screen are returned to the ultrafine grinding process for reprocessing, while the fine material under the 400 mesh screen is returned to the premixing process as core powder for regranulation. The material utilization rate in the production process reaches 100%. Testing shows that the finished filler has a particle size distribution of 100-400 mesh, an apparent density of 1.48 g / cm³, an average UV shielding rate of 91% in the 200-400 nm range, a contact angle of 28° with No. 70 asphalt at room temperature, and a migration rate of 1.6% for the active components after 48 hours of heat storage at 163℃. This step involves low-temperature granulation and closed-circuit screening to form continuously graded particles with a density close to that of commonly used limestone ore powder, thus solving the defects of large density differences in fillers leading to segregation and unreasonable gradation.

[0031] Example 2 S1 Preparation of Surface Reconstruction Calcined Coal Gangue Base Material: After crushing, coal gangue is fed into a rotary kiln and heated to 800℃ at a rate of 5℃ / min. It is then calcined for 2 hours, resulting in a residual carbon content of 0.5%. After cooling, it is ground to 200-300 mesh. The calcined coal gangue powder and sodium calcium bentonite are fed into a high-speed shear mixer at a mass ratio of 9:1. The shearing speed is set to 3500 rpm. During the shearing process, 6.5% of the powder mass of deionized water mist is sprayed in. The mixture is sheared and mixed for 10 minutes. After drying, it is ground a second time to adjust the specific surface area to 460 m² / kg. The thickness of the embedded bentonite layers is measured to be 30-40 nm, thus obtaining the surface reconstruction base material.

[0032] S2 Preparation of Loaded Anti-aging Components: After acidification and loosening, sepiolite was obtained as acidified sepiolite fibers with a porosity of 65% and a pore volume of 0.45 cm³ / g. Cerium nitrate hexahydrate was added at a loading of 20% for nano-cerium dioxide. After in-situ precipitation, the average particle size of nano-cerium dioxide was 15 nm, and the molar ratio of trivalent cerium to tetravalent cerium was 3:7. Hindered amine light stabilizer 944 with triethoxysilyl groups was added at a loading of 10% for light stabilizer grafting. After covalent grafting, the anti-aging components were obtained by centrifugation, vacuum drying, and loosening.

[0033] S3 Preparation of Interface Modified Coating Material: Waste rubber powder is ground to 1350 mesh after being desulfurized by twin-screw extruder, with a rubber powder gel content of 65%; Pre-hydrolyzed γ-aminopropyltriethoxysilane is spray-grafted onto the surface of fluidized rubber powder at a coating amount of 2.5%, and activated waste rubber powder is obtained after thermal curing.

[0034] S4 Composite Coating Molding: Weigh 58 parts by weight of surface reconstruction base material and 20 parts by weight of loaded anti-aging component (lower limit of the anti-aging component dosage range), and premix at room temperature for 5 minutes at 1500 rpm. After premixing, reduce the speed to 1000 rpm and spray 4% (by weight of powder) of cationic slow-cracking asphalt emulsion. Add 20 parts of activated waste rubber powder, increase the speed to 2500 rpm, and mix for 10 minutes while controlling the chamber temperature at 65℃. After mixing, dry at 115℃ to a moisture content of 0.7%, and obtain the finished filler through double-layer sieving. The oversize and undersize materials are recycled. Testing shows that the finished product has an apparent density of 1.38 g / cm³, an average UV shielding rate of 94%, a contact angle with asphalt of 25°, and an active component migration rate of 1.2% after 48 hours of heat storage.

[0035] Example 3 S1 Preparation of Surface Reconstruction Calcined Coal Gangue Base Material: After crushing, coal gangue is fed into a rotary kiln and heated to 850℃ at a rate of 5℃ / min. It is then calcined for 1.5h, resulting in a residual carbon content of 0.4%. After cooling, it is ground to 200-300 mesh. The calcined coal gangue powder and sodium calcium bentonite are fed into a high-speed shear mixer at a mass ratio of 9:1. The shearing speed is set to 4000rpm. During the shearing process, deionized water mist accounting for 8% of the powder mass is sprayed in. The mixture is sheared and mixed for 8min. After drying, it is ground a second time to adjust the specific surface area to 490m² / kg. The thickness of the embedded bentonite layers is measured to be 40-50nm, thus obtaining the surface reconstruction base material.

[0036] S2 Preparation of Loaded Anti-aging Components: After acidification and loosening, sepiolite was obtained as acidified sepiolite fibers with a porosity of 68% and a pore volume of 0.48 cm³ / g. Cerium nitrate hexahydrate was added at a loading of 25% for nano-cerium dioxide. After in-situ precipitation reaction, the average particle size of nano-cerium dioxide was 19 nm, and the molar ratio of trivalent cerium to tetravalent cerium was 3.2:6.8. Hindered amine light stabilizer 944 with triethoxysilyl groups was added at a loading of 12% for light stabilizer grafting. After covalent grafting, the anti-aging components were obtained by centrifugation, vacuum drying, and loosening.

[0037] S3 Preparation of Interface Modified Coating Material: Waste rubber powder is ground to 1500 mesh after being desulfurized by twin-screw extruder, with a rubber powder gel content of 62%; Pre-hydrolyzed γ-aminopropyltriethoxysilane is spray-grafted onto the surface of fluidized rubber powder at a coating amount of 3%, and activated waste rubber powder is obtained after thermal curing.

[0038] S4 Composite Coating Molding: Weigh 40 parts by weight of surface reconstruction base material and 35 parts by weight of loaded anti-aging component, and premix at room temperature for 5 minutes at 1500 rpm. After premixing, reduce the speed to 1000 rpm and spray 5% by weight of cationic slow-cracking asphalt emulsion. Add 25 parts by weight of activated waste rubber powder, increase the speed to 2500 rpm, and mix for 10 minutes while controlling the chamber temperature at 70℃. After mixing, dry at 120℃ to a moisture content of 0.6%, and obtain the finished filler through double-layer sieving. The oversize and undersize materials are recycled. The finished product has an apparent density of 1.25 g / cm³, an average UV shielding rate of 96%, a contact angle with asphalt of 22°, and an active component migration rate of 0.9% after 48 hours of heat storage.

[0039] Comparative Example This comparative example adopts the mainstream conventional modified filler scheme described in the background technology: 200-300 mesh ordinary limestone mineral powder is selected as the matrix, and 8% free nano-cerium dioxide and 3% free hindered amine light stabilizer 944 are directly added according to the mineral powder mass ratio. The modified filler is obtained by high-speed mixing at 1500 rpm for 10 min at room temperature. The preparation process did not involve surface reconstruction of coal gangue, did not use sepiolite as a carrier to load anti-aging components, and did not prepare a grafted modified waste rubber powder elastic coating layer. The filler lacked a three-layer core-shell structure. The performance was compared with that of the example using the same testing methods. The comparative filler showed an apparent density of 2.72 g / cm³, a specific surface area of ​​280 m² / kg, an average UV shielding rate of 72% in the 200-400 nm range, a contact angle of 48° with No. 70 asphalt at room temperature, a migration rate of 14.7% for active components after 48 hours of heat storage at 163℃, no continuous particle size distribution, a 22% residue rate on a 100-mesh sieve, and a 31% passing rate on a 400-mesh sieve. It was prone to stratification and segregation after mixing with asphalt.

[0040] All performance tests of the samples were conducted in strict accordance with the current highway engineering test specifications. The apparent density of the filler was tested using the volumetric flask method, the specific surface area was tested using the Blaine air permeability method, the UV shielding rate was tested using a UV-Vis spectrophotometer to measure the transmittance in the 200-400nm band and calculate the average shielding rate, the asphalt contact angle was tested using the lying drop method at room temperature of 25℃, the migration rate of the active components was determined by extracting with toluene solvent after heat storage at 163℃ for 48h, and the proportion of the total mass of precipitated cerium dioxide and light stabilizer to the total mass of anti-aging components in the filler was determined, and the particle size distribution was tested using the standard vibrating sieve method. In the performance testing of asphalt mastic, filler was added to Grade A road petroleum asphalt at a conventional mineral powder content of 30% of the asphalt mass. A uniform mastic was prepared by high-speed shearing at 4000 rpm for 15 minutes. First, a short-term thermo-oxidative aging process was performed in a 163℃ rotating thin-film oven for 85 minutes. Then, it was subjected to continuous irradiation with a 340nm ultraviolet light source at an irradiation intensity of 30W / ㎡ for 1000 hours to simulate long-term photo-oxidative aging. The penetration at 25℃, ductility at 5℃, ring and ball softening point, and rotational viscosity at 135℃ were tested before and after aging, and the performance retention rate or change rate was calculated. For the water stability of the asphalt mixture, standard Marshall specimens were prepared using AC-13 gradation. Freeze-thaw cycle tests were conducted according to specifications, and the splitting tensile strength before and after freeze-thaw cycles was tested, and the freeze-thaw splitting tensile strength ratio was calculated. Five parallel samples were set up for each indicator test. Outliers with a dispersion exceeding 10% were removed, and the arithmetic mean was taken as the final result to ensure data parallelism and comparability.

[0041] This preparation process involves two core chemical reactions. In all examples, the reaction conditions were strictly controlled to ensure that the reaction proceeded fully, and no by-products remained that affected the asphalt properties. The first reaction is the in-situ hydrolysis and precipitation of cerium nitrate hexahydrate under weakly alkaline conditions, and the reaction formula is as follows: The resulting nano-cerium dioxide particles nucleate and grow directly within the open pores of sepiolite. Due to the physical confinement of the pores, they do not undergo hard agglomeration or freely migrate and diffuse in asphalt oil, thus overcoming the defects of poor dispersibility and easy loss of free nano-cerium dioxide, which leads to a decrease in UV shielding efficiency. The second reaction is an alcoholysis grafting reaction between a hindered amine light stabilizer with triethoxysilyl groups and silanol groups on the surface of sepiolite. The reaction formula is as follows: This reaction allows the small molecule light stabilizer to be firmly anchored to the surface of the sepiolite carrier through silicon-oxygen covalent bonds, preventing it from being dissolved and leached out by saturated and aromatic fractions in the asphalt. It can exert a peroxide decomposition effect at the filler-asphalt interface for a long time, solving the defects of small molecule light stabilizers being easy to dissolve and having rapid long-term light stability degradation.

[0042] The ammonium nitrate and ethanol byproducts generated in the reaction are completely removed in the centrifugal washing and vacuum drying / hot air curing processes, with the residual amount being less than 0.1%, which will not have a negative impact on the performance of asphalt.

[0043] To visually compare the performance differences between each embodiment and the prior art, the test results are summarized in the following two data tables: Table 1 Comparison of basic physical properties of fillers in each embodiment and comparative example Table 1 Explanation: This table presents the test results of the intrinsic physical properties of the filler. The requirements for filler gradation in asphalt pavement construction are ≤5% residue rate on a 100-mesh sieve and ≤5% passing rate on a 400-mesh sieve. All three examples meet the continuous gradation requirements, while the comparative example has a large gradation dispersion. The apparent density of the examples is closer to the bulk density range of asphalt mixtures, which can reduce the risk of segregation during the construction mixing process. The specific surface area of ​​the examples is in the optimal range for asphalt adsorption, with a smaller contact angle with asphalt, better wettability, and higher UV shielding rate. Moreover, under thermal storage conditions, the migration rate of anti-aging components is reduced by an order of magnitude compared to the comparative example, effectively solving the defects of unreasonable gradation, weak interfacial bonding, and easy loss of anti-aging components in existing fillers.

[0044] Table 2 Comparison of the performance of asphalt mastic and mixture in each embodiment and comparative example Table 2 explains: This table presents the application performance results of the filler after being incorporated into the asphalt system. Higher penetration and ductility retention rates indicate lower thickening and embrittlement of the asphalt after aging. Lower softening point increment and viscosity growth rate indicate milder thermo-oxidative and photo-oxidative aging reactions. A higher freeze-thaw splitting strength ratio indicates stronger resistance to water damage at the filler-asphalt interface. The data shows that the application performance of the examples is significantly better than that of the comparative examples, verifying the effect of the three-layer core-shell structure of "rigid core-anti-aging fiber intermediate phase-elastic shell" on improving long-term aging resistance and interfacial bonding performance, effectively solving the defects of existing fillers such as long-term protective failure, easy cracking at low temperatures, and insufficient water stability.

[0045] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.

Claims

1. An aging-resistant composite modified filler for asphalt, characterized in that, By weight, it comprises the following components: 40-60 parts of surface-reconstructed calcined coal gangue base material, 20-35 parts of supported anti-aging component, and 10-25 parts of interface-modified coating layer; the surface-reconstructed calcined coal gangue base material is calcined coal gangue powder with sodium calcium bentonite flakes embedded on the surface, the supported anti-aging component is acidified sepiolite fiber with pore-loaded nano-cerium dioxide and surface-grafted hindered amine light stabilizer, and the interface-modified coating layer is ultrafine activated waste rubber powder grafted with silane coupling agent.

2. The aging-resistant composite modified filler for asphalt according to claim 1, characterized in that, In the surface-reconstructed calcined coal gangue matrix, the calcined coal gangue is obtained by calcining raw coal gangue ore at 750-850℃ for 1.5-2.5h to remove residual carbon, followed by grinding, with a grinding particle size of 200-300 mesh; the mass ratio of sodium calcium bentonite to calcined coal gangue is 1:9, the thickness of the bentonite layer embedded on the surface of calcined coal gangue is 20-50nm, and the overall specific surface area of ​​the matrix is ​​400-500m² / kg.

3. The aging-resistant composite modified filler for asphalt according to claim 1, characterized in that, In the supported anti-aging component, the acidified sepiolite fiber is a high-porosity fibrous sepiolite obtained by acidification with hydrochloric acid, washing and drying, with a porosity of not less than 60%; the loading of nano-cerium dioxide is 15%-25% of the mass of the acidified sepiolite fiber, and the average particle size of the nano-cerium dioxide is 10-20 nm; the bonded hindered amine light stabilizer is hindered amine light stabilizer 944 with triethoxysilyl groups, which is grafted onto the hydroxyl sites on the surface of sepiolite fiber through siloxane bonds, and the grafting loading is 8%-12% of the mass of the acidified sepiolite fiber.

4. The aging-resistant composite modified filler for asphalt according to claim 1, characterized in that, In the interface-modified coating layer, the ultrafine activated waste rubber powder is obtained by ultrafine grinding of waste tire tread rubber powder after stress desulfurization activation, with a grinding particle size of 1200-1500 mesh; the silane coupling agent used for graft modification is γ-aminopropyltriethoxysilane, and the coating amount of the coupling agent is 2%-3% of the mass of the ultrafine activated waste rubber powder. After grafting, the surface of the rubber powder has amino active sites that can react with the polar groups of asphalt.

5. The aging-resistant composite modified filler for asphalt according to claim 1, characterized in that, The overall particle size distribution of the composite modified filler is 100-400 mesh, the apparent density is 1.2-1.6 g / cm³, the average shielding rate in the 200-400nm ultraviolet band is not less than 90%, and the contact angle with No. 70 road petroleum asphalt at room temperature is not greater than 30°.

6. A method for preparing an aging-resistant composite modified filler for asphalt, used to prepare the aging-resistant composite modified filler for asphalt according to any one of claims 1-5, characterized in that, Includes the following steps: S1. Preparation of surface-reconstructed calcined coal gangue base material: The raw coal gangue ore is crushed to a particle size of less than 5 mm and then calcined at high temperature to remove residual carbon. After grinding, it is mixed with sodium-modified calcium-based bentonite and then subjected to high-speed shear reconstruction and secondary grinding to obtain a reconstructed base material with bentonite sheets embedded on the surface. S2. Preparation of supported anti-aging components: Acidified modified sepiolite fibers are dispersed in an ethanol aqueous solution with a volume fraction of 50%. A cerium source precursor is added to generate nano-cerium dioxide through in-situ precipitation reaction and load it into the pore structure of sepiolite fibers. Then, a hindered amine light stabilizer with triethoxysilyl groups is added to carry out a grafting reaction. After centrifugation and drying, the supported anti-aging components are obtained. S3. Prepare interface-modified coating material: waste tire tread rubber powder is activated by twin-screw stress desulfurization and then ultra-finely ground. It is then modified by spraying with silane coupling agent ethanol solution and thermally cured to obtain activated waste rubber powder micro powder. S4. Composite coating molding: Surface-reconstructed calcined coal gangue base material and loaded anti-aging components are put into a high-speed mixer for premixing. Cationic slow-cracking asphalt emulsion is sprayed as a binder. Activated waste rubber powder is added and continuously mixed at high speed so that the rubber powder adheres and coats the surface of the mixed particles. After drying and sieving, aging-resistant composite modified filler for asphalt is obtained.

7. The preparation method according to claim 6, characterized in that, The calcination temperature of the raw coal gangue ore in S1 is 750-850℃, and the calcination holding time is 1.5-2.5h. After calcination, the coal gangue is ground to 200-300 mesh by a ball mill and fed into a high-speed shear mixer at a mass ratio of 9:1 with sodium-modified calcium-based bentonite. The shearing speed is set to 3000-4000rpm. During the shearing process, 5%-8% of the mass of the mixed powder is continuously sprayed with deionized water mist. The shearing and mixing time is 8-12min. After mixing, the powder is dried to constant weight at 105℃ and then ground a second time to a specific surface area of ​​400-500m² / kg to obtain surface-reconstructed calcined coal gangue base material.

8. The preparation method according to claim 6, characterized in that, The preparation process of acid-modified sepiolite wool in S2 is as follows: raw sepiolite wool is immersed in a 1 mol / L hydrochloric acid solution with a solid-liquid ratio of 1:10, and acidified by stirring in a 60℃ constant temperature water bath for 2 hours. After filtration, it is washed with deionized water until the filtrate is neutral. After drying at 105℃ for 4 hours, it is loosened by airflow to obtain fibrous acidified sepiolite wool. The cerium source precursor is cerium nitrate hexahydrate. After its addition, the pH of the system is adjusted to 8-9 using 10% dilute ammonia water. The reaction was stirred in a constant temperature water bath for 2 hours to allow the in-situ generated nano-cerium dioxide to be uniformly deposited on the pores and surface of sepiolite fibers. After adding the hindered amine light stabilizer 944 with triethoxysilyl groups, the system was heated to 80°C and stirred for 3 hours to allow the light stabilizer to be grafted onto the hydroxyl sites on the surface of sepiolite fibers through silicon-oxygen covalent bonds. After the reaction was completed, the solid phase was separated by centrifugation at 3000 rpm for 10 minutes and then vacuum dried at 80°C for 12 hours to obtain the supported anti-aging component.

9. The preparation method according to claim 6, characterized in that, The initial particle size of the waste tire tread rubber powder in S3 is 40 mesh. It is stress-desulfurized and activated using a twin-screw extruder at 180-200℃ and a screw speed of 300 rpm. The extruded rubber compound is cooled by air and then fed into an ultrafine vibrating mill to be ground to 1200-1500 mesh. γ-aminopropyltriethoxysilane is prepared into an ethanol aqueous solution with a mass concentration of 20% and sprayed evenly onto the surface of the fluidized rubber powder. After spraying, it is cured with hot air at 100℃ for 20 minutes to allow the coupling agent to form covalent grafts with the active hydroxyl groups on the surface of the rubber powder, thereby obtaining activated waste rubber powder micron powder.

10. The preparation method according to claim 6, characterized in that, The premixing speed of the high-speed mixer in S4 is 1500 rpm, the premixing time is 5 min, and the premixing process is kept at room temperature. The solid content of the cationic slow-cracking asphalt emulsion is 50%, and the spraying amount accounts for 3%-5% of the total mass of the mixed powder. During the spraying process, the mixer speed is kept at 1000 rpm. After adding activated waste rubber powder, the mixer speed is increased to 2500 rpm, the temperature of the mixing chamber is kept at 60-70℃, and the mixing time is 10 min, so that the rubber powder is evenly coated on the surface of the core particles by the binding effect of the asphalt components in the emulsion. After the mixing is completed, the material is sent to a hot air circulating drying box and dried at 110-120℃ until the moisture content of the material is no more than 1%. The material is screened using a double-layer vibrating screen of 100 mesh and 400 mesh. The material between the two screens is used as the finished filler. The material retained on the screen is returned to the ultrafine grinding process for processing, and the fine material under the screen is returned to the premixing process for re-granulation.